MRI dynamics of brain and spinal cord in progressive multiple sclerosis. Issue 1 (January 1996) - Kidd, D; Thorpe, J W; Kendall, B E; Barker, G J; Miller, D H; McDonald, W I; Thompson, A J
Abstract : OBJECTIVE–To assess the usefulness of serial cord MRI in patients with progressive multiple sclerosis. METHODS–Monthly MRI of the brain and spinal cord with and without gadolinium enhancement was carried out in 19 patients with progressive multiple sclerosis (10 primary progressive, nine secondary progressive) over the course of one year. RESULTS–During this period there were 132 active lesions in the brain and only six in the cord. One hundred and twelve (85%) active brain lesions occurred in the secondary progressive group; three new cord lesions occurred in each group. In the secondary progressive group MRI activity was high in patients who had superimposed relapses, whereas in those who progressed without relapse and in the primary progressive group it was low. Cross sectional areas of the cord decreased at the C5 level in both groups, implying progressive atrophy of fibre tracts. There was no relation between either brain or cord MRI activity and change in disability over the study period. CONCLUSIONS–Although the detection of new lesions by frequent cord imaging using current technology has little role in the monitoring of disease activity in progressive multiple sclerosis, the serial measurement of cord cross sectional area may be important. There is also evidence to suggest that the mechanism underlying irreversible disability in patients with progressive multiple sclerosis may be different in patients who continue to relapse than in those who do not.